Saving Incentives for Low- and Middle-Income Families: Evidence from a Field Experiment with H&R Block - Duflo, E.; Gale, W.; Liebman, J.; Orszag, P.; Saez, E. (Quarterly Journal of Economics, 2006)
We analyze a randomized experiment in which 14,000 tax filers in H&R Block offices in St. Louis received matches of zero, 20 percent, or 50 percent of IRA contributions. Take-up rates were 3 percent, 8 percent, and 14 percent, respectively. Among contributors, contributions, excluding the match, averaged $765 in the control group and $1100 in the match groups. Taxpayer responses to similar incentives in the Saver's Credit are much smaller. Taxpayers did not game the experiment by receiving a match and strategically withdrawing funds. Tax professionals significantly influenced contribution choices. These results suggest that both incentives and information affect behavior.